Expression of Cadherin, an insecticide resistance associated gene in oil palm pest, Tirathaba mundella and Pollinator, Elaeidobius kamerunicus induced by exposure of Bacillus thuringiensis - Khai, Calvin Tan Zhe (2020)
Tirathaba mundella is a major pest that potentially reduce the oil palm yield in plantations established on peat soil while Elaeidobius kamerunicus is a pollinating weevil that promote oil palm pollination. Current pest management strategies targeted to control the infestation of T. mundella and maintain the population of E. kamerunicus. Bacillus thuringiensis (Bt) insecticide has since been used to control insect pest in oil palm plantation while ensuring the population of pollinating weevil will not be adversely affected. However, studies have shown the progression development of resistance against Bt toxins among many pest insects, left alone the BT resistance in T. mundella was not well studied. Prior to this study, limited molecular data were available for these species and this constraint the study of insecticide resistance at the molecular level. In this study, cadherin gene, which often associated with the resistance against Bt toxin was investigated its relative expression in both T. mundella and E. kamerunicus. Insect samples were collected from two plantation sites, one with high exposure and one with low exposure to Bt insecticide. T. mundella collected from plantation with higher exposure to Bt toxin shows significant lower cadherin expression level and lower mortality against Bt as compared to T. mundella with low exposure to Bt. Relatively lower cadherin gene expression was observed at the early development stages of T. mundella collected from the plantation with higher Bt exposure. Relatively lower cadherin gene expression may confer protection to the pest against Bt as observed in the bioassay. In E. kamerunicus, cadherin gene was not expressed and they were not affected by the application of Bt insecticide. The findings of this study lead to the inference that prolong exposure of Bt insecticide may induce the progression development of Bt¬resistance strain. Further study is needed to confirm the claim and unveil the mechanism.